Perception of nurses on the adhesion of partners of pregnant women with syphilis to the treatment - Mayanne Santana Nóbrega de Figueiredo; Edilma Gomes Rocha Cavalcante; Célida Juliana de Oliveira; Maria de Fátima Vasques Monteiro; Glauberto da Silva Quirino; Dayanne Rakelly de Oliveira (Universidade Federal do Ceará, 2015)
Objective: to investigate the perception of nurses of the Family Health Strategy on the factors that influence adhesion to treatment of sexual partners of pregnant women with syphilis. Methods: it is a qualitative research, made with 10 nurses. To collect data, a semi-structured interview was used. The data were submitted to thematic analysis. Results: the following categories were identified: the approach of the nurses to partners of pregnant women with syphilis; barriers that influence on the adhesion to the treatment; strategies and actions of adhesion of the partners in the treatment; perception of the nurse concerning the responsibility of assistance and effectiveness of the treatment. Conclusion: it was identified that nurses have a wide perception of aspects relating to adhesion to the treatment, but need better scientific and practical basis to perform effectively activities on the management of sexual partners with syphilis.